Between-session reliability and sensitivity of force production characteristics across various force-time points during the isometric single-leg long-lever bridge - Adam E. Sundh; Nicholas J. Ripley; A.J. Lamb; Conor J. Cantwell; Paul Comfort (PLoS ONE, 2026)
The purpose of this study was to assess the between-session reliability of peak force and early force-time variables in a unilateral isometric hamstring assessment (isometric long-lever bridge). The sample consisted of 30 collegiate male athletes (age: 19.4 ± 1.3 years; height: 1.79 ± 0.1 m; body mass: 80.4 ± 10.3 kg) with no history of recent hamstring injury (<6 months) who volunteered to participate in the study. All participants performed 3 unilateral maximal voluntary isometric contractions (MVIC) with their heels on force plates and shoulders elevated 15.24 cm, while their hips were secured with a loaded barbell. Data was analyzed to assess the reliability of force values at 50, 100, 150, 200, 250 ms, and peak force (N) across three repeated sessions. Moderate-good relative and absolute reliabilities were observed across all early force-time variables with lower bound ICC values ≥ 0.51 (0.51–0.71) and point estimate CV% ≤ 12.65% (7.63–12.65), with moderate relative (ICC ≥ 0.74; range 0.74–0.92) and absolute (CV% ≤ 6.50%; range 6.48–6.50) reliability for peak force. Trivial to small effect sizes ( g ≤ 0.4) were observed between sessions. These findings suggest that the isometric single-leg long-lever bridge (SL-LLB) can be used to reliably monitor peak and rapid force generating capacities to track performance changes over time due to training adaptations as well as acute or chronic fatigue.